Propuesta De Método De Costeo Para La Producción De Suelas Para Zapatos Del Fabricante Oswaldo Porras -El Caminante (2021)
According to records found in the Bogotá Chamber of Commerce, the pioneers of the leather industry in the country are mainly Julia de Rodríguez with hers, her father, Juan de Dios Restrepo, in the 1920s; Spring Step founded in 1953. The work of Morales et al. (2010) is one of the very few antecedents that exist on studies of the footwear agglomeration of El Restrepo, and there are numerous data that can be extracted from said work at the time of making an initial characterization. Previously it was very, very good to have a warehouse of these and it even gave a lot of profitability, now they are not aware that the State control entities are propending because all existing businesses in the sector are legalized and in this way avoid smuggling in the zone; However, many producers in their desire to grow and sell cheaply, many times do so without having the legal regulations applicable to the business, the legal thing that can bring them serious problems in the future, it is also known as year after year is disappearing the footwear market.